Eugene Havas and an Early Attempt at Personal Diplomacy to Normalize US-Hungarian Relations, 1960-1964 - Pál, István (Hungarian Journal of English and American Studies, 2020)
After the fall of the 1956 Hungarian Revolution and War of Independence, communist Hungary had struggled to break out of diplomatic isolation. The government formed by Secretary General of the Hungarian Socialist Workers’ Party János Kádár had not been recognized by the Western powers, including the United States of America. American- Hungarian bilateral relations, therefore, were rather strained, and before the restitution of Hungary’s full status in the United Nations Organization, the US minimized the communication between the two countries. To change this, the Hungarian Ministry of Foreign Affairs and Intelligence Service working under the aegis of the Ministry of Internal Affairs endeavored to engage expatriates—more or less famous or well-known professionals who still had some family connection to Hungary—as amateur gobetweens and semi-assets in order to find channels of communication with the American political elite and thus, via personal diplomacy, foster better relations between the two countries. The essay discusses the case of Eugene Havas (1899-1967), American economic expert and journalist of Hungarian decent. The representatives of the Kádár regime had great expectations towards him as an intermediary, this notwithstanding, as the essay will conclusively demonstrate the effect of Havas’s activities remained rather limited. (IP)